ANALISIS PENGARUH IMPOR, EKSPOR DAN INFLASI TERHADAP CADANGAN DEVISA DI INDONESIA - Hesniati Hesniati; Henliyanto Henliyanto; Ria Hartoko; Evita Kordinata; Angelina Alicia; Diavika Febriyanti (Universitas Madura, 2022)
The purpose of this study is to determine and analyze the effect of Imports, Exports and Inflation on Foreign Exchange Reserves in Indonesia. The sample used in this study collects 60 data series from January 2015 to December 2021. The dependent variable in this study was Foreign Exchange reserves, whilst the independent variables are imports, inflation and exports. To test the results of the influence in this study multiple linear regression analysis and the results of Imports, Exports and Inflation have a sig value. < 0.05 then there is a significant effect on foreign exchange reserves.